A Comparative Evaluation of Change in Surface Roughness of Aesthetic Resin Composite Restorative Material on Exposure to Different Commonly Consumed Beverages: An In vitro Study - Prabhu Varsha; Raju Chauhan (Journal of Pharmacy and Bioallied Sciences)
Background: Beverage consumption is commonly practiced by individuals of all age groups and is likewise known to cause pH alteration of the oral cavity, thereby, affecting the physical property of the restorative material like surface roughness. Aim: To assess surface roughness changes in four resin-based restorative materials (Ormocer, Giomer, Nanoceramic, and Nanohybrid composite) after exposure to commonly consumed beverages. Materials and Methods: Two hundred composite discs were divided into four groups (Giomer, Ormocer, Nanoceramic, and Nanohybrid) and immersed in five subgroups (artificial saliva, carbonated beverage, carbonated fruit-based beverage, non-carbonated fruit-based beverage, and black coffee) for 21 days. Surface roughness was measured using a surface profilometer, and statistical analysis was performed using ANOVA and Tukey’s test. Results: Nanohybrid (Group 4) exposed to carbonated beverages showed the highest roughness (Ra = 2.439 ± 0.797 μm). Nanoceramic (Group 3) exhibited the lowest roughness (Ra = 1.537 ± 0.305 mm), demonstrating superior resistance to surface degradation. Conclusion: Nanoceramic composite resin showed the least surface roughness changes and was highly resistant against all erosive beverages.